NEW DATA ON GEOCHEMISTRY OF THE OLDEST (2.95-3.05 GA) ANDESITE ASSOCIATION IN EASTERN FENNOSCANDIA - Svetov S.A. (My University, 2003)
The paper presents results of geochemical study of the oldest (2.95–3.05 Ga) andesite association of the Chalka volcanic structure, which is a member of the Archean Vedlozero–Segozero greenstone belt located in the southeastern part of the Fennoscandian Shield. The Vedlozero–Segozero greenstone belt extends longitudinally over about 300 km (width 50–60 km) and includes several local greenstone structures (Hau-tavaara, Koikary, Palasel'ga, Semch, Sovdozero, Oster, and others) [1]. The greenstone belt consists of komatiite–basalt associations (2.95–3.05 Ga) and volcanic andesitic– dacitic rocks of two age ranges (2.95–3.05 and 2.85– 2.90 Ga) [2]. Based on facies-formational analysis, ancient andesite associations of the Hautavaara make up a series of central-type paleovolcanoes (Nyal'mozero, Ignoila, Hautavaara, and Chalka) formed in a shallow marine environment [3]. The U–Pb zircon dating yielded an age of 2995 ± 20 Ma for subvolcanic andesi-dacite from the Ignoila neck [4], 3000 ± 40 Ma for sub-volcanic andesites from the Palasel'ga structure, and 3020 ± 10 Ma for subvolcanic stock from the Oster structure [5]. The most complete section of the oldest basaltic andesite–andesite–dacite association crops out in the Chalka paleovolcanic zone in the northern part of the Hautavaara structure [6, 7]. Volcanic structures are preserved in the studied rocks owing to metamorphism of the epidote–amphibolite facies (andalusite–sillimanite type). The vent zone of the Chalka paleovolcano consists of two necks, which are rimmed by boulder and agglomerate tuffs of the facies of explosive eruptions and agglomerate flows, and lenticular intercalations of flows of coarse pillow lava, clastolava, and massive lava. The latter is characterized by lumpy and amygda-loidal structures, as well as the presence of pillow brec-cia and various (boulder, agglomerate, and lapilli) tuffs. The lenticular beds are from 15 to 50–70 m thick and 500–700 m long. The northern neck consists of microporphyritic andesites in the central part, coarse-porphyritic and glomeroporphyritic andesites in the marginal parts, and agglomeratic andesites at the southern margin. The coarse-porphyritic andesidacites grade into clastolavas and pillow lavas. The southern neck of massive fine-grained andesites is confined to tuffs. The vent zone includes numerous dikes of andesites, dacites, and less common rhyolites and diorites. With increasing distance from the vent zone, lavas become more homogeneous and acid. Massive and amygdaloidal varieties, which prevail in the distal zone, intercalate with lapilli and psammitic tuffs. The lava flows are from a few meters to 40–60 m thick, where the tuff interbeds are 0.5–1.5 m thick. The total thickness of the reconstructed section of the Chalka paleovolcano is 2.5 km. The facies composition of eruption products suggests that this structure is a polygenic stratovolcano with nearly equal proportions of lavas and tuffs. In order to carry out precision geochemical study, we took the least altered samples of different facies from the entire section of the paleovolcano. The major elements were analyzed by the XRF method on a VRA-33 analyzer at the Geological Institute, Karelian Research Center. The measurement error was <3% for elements with a concentration of >0.5 wt % and 5% for elements with a concentration of <0.5 wt %. Trace and rare earth elements were analyzed by the ICP-MS method in the Analytical Laboratory of the Institute of Geology and Geochemistry, Ural Division, Russian Academy of Sciences. The measurement error was less than 2%. Classification diagrams presented in this work include previously published data on Chalka paleovolcano (80 analyses) and Ignoila paleovolcano (140 analyses) [3, 7].
Keywords: Precambrian::Archean; Докембрий::Архей